2022
DOI: 10.3390/nu14061205
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Bone Turnover Markers and Factors Associated with Metabolic Syndrome in Prepubertal Girls and Boys

Abstract: The associations between individual components of metabolic syndrome (MetS) and bone health in children are complex, and data on this topic are sparse and inconsistent. We assessed the relationship between bone turnover markers and markers of the processes underlying MetS (insulin resistance and inflammation) in a group of presumably healthy children aged 9–11 years: 89 (51 girls, 38 boys) presenting without any features of MetS and 26 (10 girls, 16 boys) with central obesity and two features of MetS. Concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…In our study, participants with MetS were characterized by a significantly higher TG/HDL-C which was the second best predictor of MetS. In contrast, fasting glucose and HbA1c levels were similar, irrespective of MetS occurrence, as indicated in our previous study on children [21]. The correlation between GGT activity and lipid biomarkers (TG and TG/HDL-C), the significant increase in these two biomarkers towards higher GGT activity in tertiles (p = 0.018), but most importantly the association of postprandial changes with the presence of MetS, allow us to suggest that GGT level may indicate metabolic disturbances associated with lipid metabolism in children with MetS.…”
Section: Discussionsupporting
confidence: 79%
“…In our study, participants with MetS were characterized by a significantly higher TG/HDL-C which was the second best predictor of MetS. In contrast, fasting glucose and HbA1c levels were similar, irrespective of MetS occurrence, as indicated in our previous study on children [21]. The correlation between GGT activity and lipid biomarkers (TG and TG/HDL-C), the significant increase in these two biomarkers towards higher GGT activity in tertiles (p = 0.018), but most importantly the association of postprandial changes with the presence of MetS, allow us to suggest that GGT level may indicate metabolic disturbances associated with lipid metabolism in children with MetS.…”
Section: Discussionsupporting
confidence: 79%
“…Bilinski et al reported that CRP was a good predictor of MetS in males, but not in females. Unfortunately, the designs of the included studies did not allow us to address this issue [50]. Due to the fluctuations in information regarding this topic, and the uncertainty in the data we obtained, we cannot issue a statement regarding the usage of hsCRP in distinguishing obesity from MetS.…”
Section: Discussionmentioning
confidence: 95%
“…This cross-sectional study included 144 children aged 9–11, randomly selected from a cohort of 284 primary school children enrolled in a previous study [ 13 ]. In the study group, MAFLD was recognized in 43 subjects, based on the below described criteria.…”
Section: Methodsmentioning
confidence: 99%
“…Pediatric reference intervals for age and sex, related to the instrumentation and applied methodology, with URL ≥ 22 IU/L and ≥24 for ALT in girls and boys, GGT ≥ 16 IU/L and AST ≥ 36 IU/L were accepted according to Adeli et al [ 17 ]. BMI percentile classifications were performed in accordance with the guideline: overweight ≥ 85 and <95; obesity ≥ 95 percentile [ 13 ]. Central obesity was defined by a waist circumference (≥90th percentile of WC by sex and age for European population), increased blood pressure as SBP ≥ 90th percentile of BP by sex, height and age [ 13 ].…”
Section: Methodsmentioning
confidence: 99%